A comprehensive study on thermal storage characteristics of nano-CeO2 embedded phase change material and its influence on the performance of evacuated tube solar water heater. (December 2020) - Kumar, P. Manoj; Mylsamy, K.
Abstract: This work examines the enhancement in thermal storage properties of the new kind of nano-embedded phase change materials (NEPCMs), which were prepared by diffusing CeO2 nanoparticles in three mass fractions such as 0.5%, 1.0%, and 2.0% in paraffin, respectively. The synthesized NEPCMs had experimentally tested with field emission scanning electron microscope (FESEM), differential scanning calorimetry (DSC), thermal properties analyzer, and Fourier transform infrared spectrometer (FT-IR). Subsequently, the performance of water-in-glass evacuated tube solar water heater was investigated, under the influence of paraffin and NEPCMs. The experiments were conducted in five cases, namely, without PCM, with paraffin as PCM, and the last three cases with three different mass fractions of CeO2 nanoparticles in NEPCMs under real-time solar exposure between 6.00 a.m. and 6.00 p.m. The performance was studied using the first law and the second law efficiencies. It is exhibited that the thermal storage characteristics of the paraffin have been enriched significantly with the dissemination of CeO2 nanoparticles. Likewise, the experimentations with solar water heater ascertained that the assimilation of paraffin and NEPCMs enhanced the first law and the second law efficiencies of the system, impressively. Furthermore, the NEPCM containing 1.0% of CeO2 nanoparticles has found to be the precise combination. Highlights: Nano-CeO2 embedded PCMs (NEPCM) were synthesized and characterized. The prepared nano-CeO2 embedded PCMs were found to have improved thermal energy storage characteristics. Nano-CeO2 embedded PCMs were integrated with an evacuated tube solar water heater. The NEPCM integrated solar water heater was investigated based on energy and exergy efficiencies. Solar water heater exhibited the better performance with nano-CeO2 embedded PCMs.